2005
DOI: 10.1007/s00422-005-0041-9
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic and stochastic features of rhythmic human movement

Abstract: The dynamics of rhythmic movement has both deterministic and stochastic features. We advocate a recently established analysis method that allows for an unbiased identification of both types of system components. The deterministic components are revealed in terms of drift coefficients and vector fields, while the stochastic components are assessed in terms of diffusion coefficients and ellipse fields. The general principles of the procedure and its application are explained and illustrated using simulated data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…4 and 5. These results are consistent with those of previous studies on stochastic human behavior [22], [23], [21] in similar contexts.…”
Section: Discussionsupporting
confidence: 83%
“…4 and 5. These results are consistent with those of previous studies on stochastic human behavior [22], [23], [21] in similar contexts.…”
Section: Discussionsupporting
confidence: 83%
“…We do this by processing data like that shown in Fig. 2 to extract estimates of the terms involved in stochastic DEs (SDEs) for χ and Φ using the techniques in Gradišek et al (2000) (see also Friedrich et al (2000), Laing et al (2007), van Mourik et al (2006)). These SDEs will form our macroscopic model, and are assumed to linearly combine purely deterministic and purely stochastic components, i.e.…”
Section: Deriving a Macroscopic Model Choosing Macroscopic Variablesmentioning
confidence: 99%
“…This is due to the fact that standard measures of movement variability reflect both noise and attractor strength (Court et al 2002). Frank et al (2003Frank et al ( , 2004 and Mourik et al (2006) have recently begun investigating whether the methods developed by Friedrich, Peinke and colleagues (e.g., Friedrich et al , 2000 can identify the deterministic (attractor strength) and stochastic (noise) components in rhythmic movement data. For example, van Mourik et al (2006) derived a method that involves inspecting movement trajectories in phase space and determining deterministic components in terms of drift coefficients and vector fields, and stochastic components in terms of diffusion coefficients and ellipse fields.…”
Section: Introductionmentioning
confidence: 97%
“…Frank et al (2003Frank et al ( , 2004 and Mourik et al (2006) have recently begun investigating whether the methods developed by Friedrich, Peinke and colleagues (e.g., Friedrich et al , 2000 can identify the deterministic (attractor strength) and stochastic (noise) components in rhythmic movement data. For example, van Mourik et al (2006) derived a method that involves inspecting movement trajectories in phase space and determining deterministic components in terms of drift coefficients and vector fields, and stochastic components in terms of diffusion coefficients and ellipse fields. A number of other researchers have also suggested that recurrence analysis can be used to isolate changes in movement variability caused by a change in noise and attractor strength independently [first by Pellecchia et al (2005) and Shockley (2002) then by Shockley and Turvey (2005) and Richardson et al (2005)].…”
Section: Introductionmentioning
confidence: 98%